Forward single‐cell sequencing into clinical application: Understanding of cancer microenvironment at single‐cell solution - Xuanqi Liu; Charles A. Powell; Xiangdong Wang (Wiley, 2022)
Abstract The single‐cell RNA sequencing (scRNA‐seq) is considered as an important approach to understand molecular mechanisms of cancer microenvironmental functions and has the potential for clinical and translational discovery and development. The recent concerns on the impact of scRNA‐seq for clinical practice are whether scRNA can be applied as a routine measurement of clinical biochemistry to assist in clinical decision‐making for diagnosis and therapy. Pushing single‐cell sequencing into clinical application is one of the important missions for clinical and translational medicine (CTM), although there still are large number challenges to be overcome. The present Editorial as one of serials aims at overviewing the history of scRNA‐seq publications in CTM, sharing the understanding and consideration on cancer microenvironment at single‐cell solution, and emphasizing the objective to translate scRNA‐seq into clinical application. The dynamic characteristics and patterns of single‐cell identity, regulatory network, and intercellular communication play decisive roles in properties of microenvironment, malignancy and migrative capacity of cancer cells, and defensive capacity of immune cells. The microenvironmental single‐cell transcriptomic profiles and cell clusters defined by scRNA‐seq have great values to explore molecular mechanisms of diseases and predict cell sensitivities to therapy and patient prognosis.